KONSENTRASI VFA DAN N-NH3 RUMPUT GAJAH MINI (Pennisetum purpureum cv. Mott) YANG DIPUPUK ORGANIK SERTA NPK SECARA IN VITRO - Afriska, Helmy Candra; Prayitno, Caribu Hadi; Hidayat, Nur (ANGON: Journal of Animal Science and Technology, 2020)
Background. The study entitled "Concentration of VFA and N-NH3 Mini Elephant Grass (Pennisetum Purpureum Cv. Mott) Fertilized Organic and NPK in Vitro" was carried out on August 1 to September 7, 2019 at the Experimental Farm and Laboratory of Animal Food Sciences, Faculty of Animal Husbandry, University Jenderal Soedirman, Purwokerto. The purpose of this study was to examine the effect of providing optimum levels of combination of manure and NPK in terms of VFA and N-NH3 concentrations of mini elephant grass. Materials and Methods. The material used in this research is the fifth mini elephant defoliation grass plant which was originally planted on a total land area of 278 m2 with the area of each plot or unit is 5 m2 and a spacing of 0.75 mx 0.35 m so that it takes 720 mini elephant grass cuttings or 20 cuttings / unit, 270 kg of manure, 2.5 kg of NPK fertilizer. The method used is factorial pattern experiments with randomized group design. The first factor is manure (O) consisting of O0: manure 0 kg / 5m2, O1: manure 7.5 kg / 5m2, O2: manure 15 kg / 5m2 and the second factor is NPK fertilizer (N) consisting from N0: NPK fertilizer 0 g / 5m2, N1: NPK fertilizer 37.5 g / 5m2, N2: NPK fertilizer 75 g / 5m2 and M3: NPK fertilizer 112.5 g / 5m2. The variables measured were the fifth VFA and N-NH3 content of mini defoliation elephant grass. Results. The results of the analysis of variance showed that the interaction between the combination of manure and NPK had no significant effect (P> 0.05), but NPK had a significant effect (P <0.05) on the VFA content and had a significant effect (P <0.05) on the content of N-NH3 mini elephant grass. Conclusion. The single effect of NPK fertilizer can significantly increase VFA and N-NH3 content. The interaction treatment of manure and NPK did not have a significant effect on the VFA and N-NH3 content of mini elephant grass.